Keanekaragaman Jenis Tumbuhan di Taman Cerdas Kota Samarinda - Azizah, Nur; Utami, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
Urban areas that have a high population density and availability of motorized vehicles required Green Open Space. Green Open Space is an open area in nature that contains vegetation which are necessary to support the ecological system and improve the environmental quality in urban areas. The purpose of this research is to identify the species and abundance of plant in Taman Cerdas Kota Samarinda. The applied method was cruise method by exploring the trails in Taman Cerdas. Every plant that are encountered are noted for the name of species and counted the number from each species. The results showed 21 species of plants consisting of 5 species of trees, 9 species of shrubs and 7 species of herbs included in 19 families with a total number of 3,704 individuals. Plants that are dominant is an ornamentals plants for aesthetic function and serve for natural therapy (healing service). The results of environmental factor measurements are Taman Cerdas located in elevation of 5 mdpl, coordinate S 0Â° 28' 32